Academic Problems Facing University Students under the Corona pandemic from Their Viewpoints - AL-Momani, Mohammad Omar; Alrabadi, Insaf George; Al-Mzary, Maaly Mefleh; Danaa, Hanaa Mustafa; Al-Jarah, Smah Suleiman (IJERI: International Journal of Educational Research and Innovation, 2023)
The study aimed to identify the academic problems facing university students during the Corona pandemic from their viewpoints and its relationship to some variables, as the study sample comprised (4000) male and female students from Jordanian universities. The study concluded that the students’ academic problems during the Corona pandemic were average in all fields of study. The study showed the absence of statistically significant differences in the students’ academic problems attributed to gender (male, female), specialization (scientific, humanitarian) and academic level (diploma, bachelor) variables.